KONSEP WILÂYAH AL-FAQÎH DALAM SISTEM POLITIK SYI`AH IMAMIYAH - Lukpinius Lukpinius (Sekolah Pasca Sarjana IAIN Bengkulu, 2016)
Abstract: The Concept Ofwilayatal-Faqih In The System Of Shia Imami. This article discusses the concept of wilayatal-Faqih in the system of Shia Imamia and its implementation in the state leadership. Research type used is library research and the method used in this research is qualitative descriptive. From the results of this study found that in view of the Shi’a Imami, there is a strong link between the concept of Imamat and Wilayatal- Faqih concept. Both are the successor to the prophetic mission of religion in order to preserve and manage the affairs of the world. If the imam is obliged to guide people after the end of the “cycle of revelation,” meaning after the death of the Prophet, then the duty of faqih is to guide people after the end of “Imamate cycle”. The differences between Imam and al-faqih are; if the imam are Ma’shum (avoid from sin), while the faqih does not ma’shum or have other special attributes similar to those of the Imam. But Al-Faqih has a position in the state if the executive and judicial powers are in Wilayatal-faqih who perform the function as representative of the imam, the legislative power belongs fully to God. Therefore, governments in the wilayatAl-Faqih also be referred to as “the law of God’s rule over man”. Parliament is required to draw up programs for various ministries based on the teachings of Islam and determine the form of government services across the country. Thus, in the system of Wilayahal-Faqih, the scholars of al-faqih has a position, both as the guardian, interpreter and executor of the laws of God.